Spectrum and states of the BCS Hamiltonian with sources - Petrina, D.Ya. (Український математичний журнал, 2008)
We consider the BCS Hamiltonian with sources, as proposed by Bogolyubov and Bogolyubov, Jr. We prove that the eigenvectors and eigenvalues of the BCS Hamiltonian with sources can be exactly determined in the thermodynamic limit. Earlier, Bogolyubov proved that the energies per volume of the BCS Hamiltonian with sources and the approximating Hamiltonian coincide in the thermodynamic limit. Розглянуто БКШ гамільтоніан з джерелами, який був запропонований Боголюбовим та Боголюбовим (мол.). Доведено, що власні вектори та власні значення БКШ гамільтоніана з джерелами можна визначити точно в термодинамiчнiй границі. Раніше Боголюбовим було встановлено, що питомі енергії БКШ та апроксимуючого гамільтоніанів збігаються в термодинамічній границі.